Evaluation of growth and biomass productivity of marine microalga Nannochloropsis sp. cultured in palm oil mill effluent (POME) - Hadiyanto, Hadiyanto; Soetrinanto, Danny; Silviana, Silviana; Mahdi, Muhamad Zaini; Titisari, Yasinta Nikita (2017)
The objective of this study was to evaluate the growth and productivity of marine algae Nannochloropsis sp. cultured in palm oil mill effluent (POME) medium. The POME was varied in concentration of 10%, 30%, and 50% (vol POME/vol water) while the comparison with fresh and saline medium was also investigated. The relative performance of the different concentrations of fresh POME were investigated with respect to their productivity, specific growth rate and biomass production. Nannochloropsis sp. cultured in 30% (v/v) fresh POME had significantly (p<0.05) higher growth rate (0.31 ± 0.06) d?1 and productivity (0.034 ± 0.01) g â?? L?1 d?1) as compared to fresh medium and other treatments (10% and 50% v/v). These results indicated the potential of microalga Nannochloropsis sp. for biomass production and POME nutrients removals. Further research on optimizing biomass productivity and nutrients removal in POME medium should be done prior to its scale up for industrial application. (Author's abstract).